Global Approximate Controllability of Quantum Systems by Form Perturbations and Applications - Balmaseda, Aitor; Lonigro, Davide; Pérez-Pardo, Juan Manuel (SIAM Journal on Control and Optimization, 2025)
We provide sufficient conditions for the approximate controllability of infinite-dimensional quantum control systems corresponding to form perturbations of the drift Hamiltonian modulated by a control function. We rely on previous results on controllability of quantum bilinear control systems and obtain a priori L1-bounds of the controls for generic initial and target states. We apply a stability result for the nonautonomous Schrödinger equation to extend the results to systems defined by form perturbations, including singular perturbations. As an application of our results, we prove approximate controllability of a quantum particle in a one-dimensional box with a point-interaction with tuneable strength at the center of the bo
Keywords: quantum control on infinite dimensions; time-dependent domains; form perturbations; nonautonomous Schrödinger equation